Blacklisting Social Science Departments with Poor Ph.D. Submission Rates - Colombo, Richard A.; Morrison, Donald G. (Management Science, 1988)
In an attempt to reduce the time taken by social science Ph.D. candidates to obtain their degrees, the Economic and Social Science Research Council (ESRC) of the United Kingdom has decided to withhold funds from social science departments of academic institutions with the poorest Ph.D. submission “rates.” Institutions with less than one in ten of their Ph.D. students submitting a thesis within four years of registration will be placed on a blacklist. In interpreting the observed submission rates the ESRC appears not to have taken account of the different numbers of registered students in social science departments, which have cohort sizes ranging from 2 to 79. This failure has potentially counter-productive consequences. An empirical Bayes method is proposed that adjusts estimates of submission rates by taking into account the number of students. The method suggests that differences in true unobservable submission rates between institutions are small and thus observable submission proportions alone do not form a good basis for policy action.